Investigating the potential of cobalt-doped zinc oxide (Zn1-xCoxOδ) as a buffer layer for CZTS thin-film solar cells - Abdullah, Huda; Xian, Kang Jian; Amir Hamzah, Muhammad Nurhayat; Mohammad Naim, Norshafadzila (Springer, 2024)
Copper zinc tin sulfide (CZTS) solar cells are one of the most promising possible substitutes for chalcopyrite copper indium gallium selenide (CIGS) in the future photovoltaic industry. This work reports on the preparation and characterization of a cobalt-doped zinc oxide (Zn1-xCoxOδ) thin-film buffer layer using the spin-coating technique on ITO back contact glass substrates. The effect of cobalt-doped zinc oxide on the structural, optical, morphological, and electrical properties of the obtained films has been investigated. The prepared thin-films were analyzed by several different characterization techniques such as X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), ultraviolet–visible (UV–Vis) spectroscopy and current density–voltage. (J-V) measurements. XRD analysis indicates all Zn1-xCoxOδ buffer layer films possess the wurtzite hexagonal polycrystalline structure with orientation (0 0 2). The images from FESEM analysis indicate the cross-sectional area and internal structure of Zn1-xCoxOδ buffer layer. The UV–Vis optical band gaps of the films were found to be in the range of 3.53–3.97 eV. The electrical analysis shows that the conductivity of cobalt-doped ZnO increases compared to the pure ZnO film without doping. The highest power conversion efficiency (PCE) of Zn0.91Co0.09Oδ is 0.54%. The analysis on cobalt-doped ZnO film showed that cobalt and zinc oxide are good candidates and potential for optoelectronic applications such as the production of solar cells which involved transparent electrodes.